Evidence for changes in carbon isotopic fractionation by phytoplankton between 1960 and 2010 - Young, J; Bruggeman, J; Rickaby, R; Erez, J; Conte, M (2013)
Rising CO2 is expected to drive a myriad of environmental changes in the surface ocean. Deciphering the phytoplankton response to this complex change is difficult. Here we determine whether a trend in the biological fractionation of stable carbon isotopes (εp) has occurred over the past 50 years. εp is primarily controlled by the acquisition and intracellular transport of inorganic carbon and the rate of carbon fixation. In turn, these processes are sensitive to phytoplankton physiology, community composition, and notably inorganic carbon availability. εp may therefore carry a signal of biological response to climate change. Temporal and spatial records of εp can be deciphered from the difference between the stable carbon isotopic composition of particulate organic matter (δ13CPOC) and that of the ambient inorganic carbon pool (δ13CCO2). Here we establish a global record of εp extending from the 1960s to today, extracted from a newly compiled data set of global measured δ13CPOC and part measured/part climatology δ13CCO2. We find that εp has changed significantly since the 1960s in the low- to mid-latitude surface ocean. The increase is most pronounced in the subtropics, where it is estimated at > 0.015‰ per year. Our findings of such rates of change are further supported by a high resolution temporal record from a single sediment trap near Bermuda. Our results are consistent with the idea that εp is affected by increased inorganic carbon availability driven by the rise in atmospheric CO2.©2013. American Geophysical Union. All Rights Reserved.